Body Weight, Cholesterol Changes and Sub-Chronic Toxicity of Mice Treated with An Emulsion Product Rich in b-Carotene - Bohari Bohari; Fenny Dian Lestari; Anton Rahmadi (Molecular and Cellular Biomedical Sciences, 2020)
Background: One of the conditions for releasing standardized herbal medicines is the presence of pre-clinical testing that can be conducted with mice. Emulsion products with the main composition of pumpkin, red palm oil, and dragon fruit have high levels of β-carotene. The purpose of this study was to observe changes in weight, cholesterol, and sub-chronic toxicity from mice treated with emulsion products.Materials and Methods: Mice observed consisted of 6 groups: (1) untreated control (given standard ration); (2) negative control (given standard ration and 2.8% (v/b) egg yolk); (3) positive control (given standard ration and 0.4% (v/b) β-carotene); (4) standard ration, 0.4% (v/b) β-carotene and 2.8% (v/b) egg yolk; (5) given a standard ration and 2% (v/b) emulsion products; and (6) given a standard ration, 2% (v/b) emulsion products and 2.8% (v/b) egg yolk. Observations of sub-chronic toxicity were done by measuring creatinine levels, kidney weight, and visual observation of kidney swelling.Results: The use of β-carotene-rich emulsions does not cause a decrease in the average weight of mice. In general, β-carotene and emulsion can overcome cholesterol increases on the 7th day, but not for the 15th day as a result of standard food intake. The increase in creatinine levels only occurs in mice treated with egg yolk control. The additional treatment of β-carotene and emulsion successfully prevents the increase in creatinine levels.Conclusion: Emulsion products did not cause changes in weight, were able to reduce cholesterol levels in a limited manner and were not toxic to mice.Keywords: cholesterol changes, sub-chronic toxicity, b-carotene, emulsion